The Effect of Managerial Ownership and Institutional Ownership on Firm Value: Environmental Disclosure as a Mediating Variable - Irma Suryahani; Tri Widayati (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Firm value is a key indicator in assessing the success and attractiveness of investments, which is determined not only by financial performance but also by governance and environmental responsibility. Ownership structure, particularly managerial and institutional ownership, is believed to mitigate agency conflicts and promote corporate transparency. However, previous empirical findings have shown mixed results; therefore, this study attempts to examine the effect of managerial and institutional ownership on firm value, with environmental disclosure as a mediating variable. The study used a quantitative approach with secondary data in the form of financial statements and annual reports of companies listed on the Indonesia Stock Exchange for the period 2022–2024. The analysis was conducted using the Partial Least Squares–Structural Equation Modeling method using SmartPLS 4. The results show that managerial and institutional ownership have a positive effect on environmental disclosure, which in turn increases firm value. Furthermore, environmental disclosure acts as a mediating variable that strengthens the relationship between ownership structure and firm value. These findings emphasize the importance of environmental disclosure practices as a sustainability strategy that not only enhances corporate legitimacy but also strengthens investor confidence and competitiveness in the capital market.